Contraction of EST in Latin - Pezzini, G (2011)
The paper analyses the contraction of est (-st). This phenomenon is generally known as 'prodelision' or 'aphaeresis' and is considered a metrical sandhi phenomenon, graphically expressed only in early Latin texts. After the introduction (1), the paper presents the first systematic collection of the evidence for this form (2), followed by a phonological discussion (3), and by the conclusions (4), which aim to show that this was a more complex and widespread phenomenon than is normally believed, and to introduce its significance for other general linguistic topics such as cliticisation, the semantics of sum, and the position of the Latin verb in the clause. © The Philological Society 2011.